A patient with mushroom allergy; a new etiological agent of Kounis syndrome - AYDINER, ELİF; BARIŞ, SAFA (TURKISH ASSOC TUBERCULOSIS & THORAX, 2016)
Kounis syndrome (KS) is a rarely diagnosed condition which should always be kept in mind when an acute myocardial infarction (AMI) happens in the context of anaphylactic reactions. We report a case of a 31-year old female; 2 hours after the ingestion of the mushroom (Pleurotus ostreatus); she experienced nausea, stomachache, vomiting, dyspnea and chest pain. Electrocardiogram (ECG) showed an ST segment elevation in D1, AVL, precordial leads V1-V4. The blood analysis revealed high levels of CK-MB fraction and troponin T values. The diagnosis of Kounis syndrome was made in the catheterization laboratory via the complete resolution of angina, along with electrocardiographic changes that took place after intracoronary nitrate therapy and skin prick to prick test positivism with the mushroom. To the best of our knowledge, this is the first case of a type I variant of Kounis syndrome due to Pleurotus ostreatus allergy reported so far.
Keywords: Anaphylaxis; coronary hypersensitivity disorder; kounis syndrome; mushroom allergy; myocardial ischaemia/infarction; PLEUROTUS-OSTREATUS; HYPERSENSITIVITY